Performance prediction equation for the Valencia Marathon based on time and pacing in the half marathon - Oficial-Casado, Fran; Priego-Quesada, Jose Ignacio; Pérez-Soriano, Pedro (Frontiers in Physiology, 2026)
IntroductionAlthough pacing is a variable that affects marathon running performance, there is a lack of studies that assessed whether it can improve performance prediction. The aim was to calculate a linear regression model with data such as the half marathon race time, age category, sex and pacing range (difference between the maximum and minimum relative speed of the half marathon) to predict the marathon time. Moreover, the accuracy of the prediction equation obtained was compared with the Daniels’ VDOT.MethodsA total of 8.261 runners, who participated in both events (Valencia Half Marathon and Marathon) in the same year, for the 2022 and 2023 editions, and ran the half marathon faster than the marathon, were included in the study. Three linear regression models were obtained: a first model with only the half marathon time and sex, a second model adding the age category to these, and a final model adding the pace range to the previous ones. Afterwards, the most accurate and simple model was selected, and its fitting was compared with respect to a model contrasted by the literature, the VDOT.ResultsThe introduction of the pace range variable did not improve the model’s prediction, obtaining an explained variance of 85% and an mean absolute error of 5.9%. The overall accuracy of the model obtained was similar to that of the VDOT system, but the models behaved differently depending on the level of runners’ performance.DiscussionThese results allow coaches and runners to establish specific training rhythms to work on the competition pacing.